SIMULATNEOUS INTERPRETING STRATEGIS FOR PRESIDENTIAL SPEECH - Wirawan, I Gede Nika (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2014)
There are many obstacle faced by the interpreter in interpreting a speech from Indonesian into English and vice versa. Because of that, the writer conducted a study and research about the appropriate strategies that could be used by the interpreter to produce a proper interpretation. The method of collecting data used in this research is observation and the method of collecting the data is qualitative. The data source used in this research is the speech of the President of Indonesia, Dr. Susilo Bambang Yudhoyono in the opening ceremony of 19th ASEAN Summit in Bali. Based on the result, it could be concluded that there are six stretegies that could be used by the interpreter, i.e., understanding the main ideas of the speech, identify the main ideas of the speech, convey the nuances and the intensity of the feelings expressed which would be different in different type of text, analyze the linking words of the speech correctly, train for a good memory and train for re-expression what the ideas in the speech.
Keywords: simultaneous interpreting, strategies for interpreter